Prospecção de microorganismos produtores de polihidroxialcanoatos e biosurfactantes em solo florestal e em lodo ativado - Silva, Amanda Lys dos Santos (2016)
Polyhydroxyalkanoates (PHAs) are polyesters produced and degradable by prokaryotes, while biosurfactants/bioemulsifiers (BS/BE) are metabolites that reduces surface tension and synthesized by this group of organisms. Interest in the potential industrial applications for PHA and BS/BE has increased due to its eco-friendly appeal. In this study, 24 bacterial colonies were isolated from Atlantic forest soil and agro-industrial sludge (Coruripe-AL, Brazil) in minimum mineral medium, as indicative of the possible ability to synthesize PHA. All strains were submitted to biochemical characterization, while the phaC gene amplification showed that isolates BMA-05, BMA-10, BMA-13 and BDL-07 can express the key enzyme for the synthesis of PHA (PHA synthase). Sequencing of the partial 16S r-DNA region was able to identify these bacteria respectively as Pseudomonas fluorescens, Enterobacter aerogenes, Klebsiella oxytocaand Bacillus pumilus. The PHAs produced by each isolate were extracted with hot chloroform and the polymeric films were obtained. Experiments in shaken flasks (0 – 96 h) were conducted to compare the biomass, total reducing glycides, pH, and total protein in minimal medium containing different contents of glucose and peptone. Supplementation with peptone was able to induce the growth of these strains, and cell-free supernatant from the cultivation of Pseudomonas fluorescens BMA-05 showed no acidification in any of the conditions tested. To polyhydroxybutyrate production (evaluated after 24 h incubation), minimal medium was used with different nitrogen sources: ammonium acetate, ammonium chloride, ammonium nitrate, sodium nitrate, ammonium sulfate, beef extract, yeast extract, glycine and peptone. The maximum accumulation of P (3HB), detected by UV-visible spectrophotometry, was obtained for P. fluorescens, E. aerogenes, K. oxytoca and B. pumilus grown in ammonium sulfate, ammonium chloride, meat extract and nitrate sodium, respectively. Observations in transmission electron microscope showed Pseudomonas fluorescens BMA-05 with eletronlucent granules when the strain was cultivated in the presence of ammonium sulfate or sodium nitrate. Although no granule was observed for the other strains in the presence of ammonium sulfate, the gas chromatography analysis confirmed the production of P (3HB). When exoenzymes expression tests were conducted, the results indicated that the strains were able to hydrolyse gelatine, starch and Tween 80, and B. pumilus caused hemolysis of sheep blood. Experiments for biosurfactant/bioemulsifier production indicate that E. aerogenes BMA-10 excreted a compound surfactant which collapses the hydrophobic surface and emulsifies the hydrocarbons kerosene, toluene, diesel oil and soybean oil. The emulsification index (E24) using the cell-free supernatant of this microorganism was thermally stable in toluene, but not in kerosene. Similar results were obtained when the pH of this microorganism cell-free supernatant was adjusted to 2, 7 and 10, as well as different concentrations of NaCl (2, 6, and 10 %) were added to the samples. These results reveal the potential of Enterobacter aerogenes BMA-10 as a P(3HB)-producing, and its growth medium free of cells an emulsifier for biotechnological purposes and also in bioremediation.